Variação linguística no ensino de Língua Portuguesa: análise das crenças e ações linguísticas de professores dos anos iniciais - Costa, Aline Cristina Nascimento da Silva (2025)
Addressing issues related to linguistic variation in the Portuguese Language (PL) classroom is necessary because the teaching of this subject is commonly based on prioritizing Traditional Grammar (TG). This pedagogical practice can lead many native speakers to become victims of linguistic prejudice. Thus, for this research, our general objective is to investigate how Portuguese language teachers in the 2nd year of Elementary School (early years) at a public school in the city of Fortaleza understand the content on linguistic variation, focusing on their beliefs and actions, aiming at inclusive pedagogical practices, based on a didactic sequence with the text genre Invitation. As specific objectives, we intend to: 1) Investigate the perception of the Portuguese language teachers participating in the research on the importance of addressing content on linguistic variation in the educational context of the 2nd year of Elementary School (early years) at a public school in Fortaleza, in the construction of the relationship between language and society; 2) To discuss the phenomenon of linguistic variation, relating standard norms and linguistic varieties, based on a didactic sequence (DS) with the text genre Invitation; 3) To analyze the understanding of content about linguistic variation, focusing on the beliefs and actions of teachers, aiming at inclusive pedagogical practices, on the part of the teachers participating in the research, based on the development and implementation of a Didactic Sequence with the text genre Invitation. We will base our theoretical foundation on Sociolinguistics, with epistemological affiliation in Labov (1972; 2008), as well as in Antunes (2007; 2009; 2010), Bagno (1999; 2001; 2003; 2007; 2009; 2013), Bortoni-Ricardo (2004; 2005), Martelotta (2011), Labov (2008); among others, on which we will base our analysis. Regarding methodology, the approach of this investigation will be qualitative, descriptive, and applied in nature, focused on action research, through an intervention proposal structured in a Didactic Sequence, as proposed by Dolz, Noverraz, and Schneuwly (2004). The data generation procedures followed these steps: 1) application of a pre-test to gauge the prior knowledge and conceptions of the teachers participating in the research regarding the content related to the theme of linguistic variation; 2) development and application of a didactic sequence and activities related to linguistic variation; 3) application of a post-test to investigate the content learned. The analysis procedures involved the analysis of the corpus, which is composed of the pre-test and the post-test, focusing on teachers'3 beliefs and actions, as well as their conception of linguistic variation in Portuguese language classes. The results showed that there were changes in the conception that the teachers participating in this research had about the phenomenon of linguistic variation in Portuguese language classes.